Silver Impact on the Growth Rate of an SDS-degrading Pseudomonas sp. strain Maninjau1 Explored using Predictive Models (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2023)
The use of silver nanoparticles in fabrics in conjunction with detergent in washing may release silver ions that can inhibit detergent remediation by microorganisms. The SDS-degrading bacterium, Pseudomonas sp. strain Maninjau1, showed prominent inhibition in the presence of silver ion. When exposed to varying silver concentrations, the bacterium's growth followed a sigmoidal pattern, exhibiting lag periods ranging from 2.5 to 5.5 hours, as modeled using the modified Gompertz model. Increasing the silver concentrations progressively slowed bacterial growth, with concentrations as low as 1.0 mg/L halting bacterial growth rate altogether. To assess these effects, the modified Gompertz model was used to determine growth rates across different silver concentrations. The results were then evaluated against several models, including the modified Han-Levenspiel, Wang, Liu, Shukor, modified Andrews, and Amor models. The Amor model did not adequately fit the growth curves. Statistical analysis revealed that the modified Han-Levenspiel model performed best, as indicated by the lowest RMSE and AICc values, the highest adjusted correlation coefficient (adR2), and AF and BF values closest to unity. The Liu, Shukor, modified Andrews, and Wang models followed in descending order of performance. The parameters obtained from the modified Han-Levenspiel model, which are max (h-1) and Ccrit (mg L-1) and m which represent maximum growth rate, critical heavy metal ion concentration and empirical constant values were 0.196, 1.1134 and 0.632, respectively. The modified Han-Levenspiel model effectively predicts the critical concentrations of heavy metals that can completely inhibit bacterial growth. This robust modeling approach highlights the model's suitability for forecasting the impact of silver on the growth dynamics of Pseudomonas sp. strain Maninjau1, particularly under conditions of toxic stress.
Keywords: SDS-degrading bacterium; Pseudomonas sp.; Silver; Inhibition; Shukor model